Do stock markets witness instantaneous reactions to changes in dividend tax laws?: Evidence from India. (30th July 2019) - Aggarwal, Shobhit; Tiwary, Mrityunjay Kumar
In this paper, we examine whether the dividend tax law changes in India in 2002 cause any instantaneous stock price reactions. Using high frequency data, we devise a novel method to segregate the impact of a particular stimulus from a series of stimuli. We show that investors did not react instantaneously to the dividend tax law changes. We examine four alternative explanations for this result: first, the demand for dividend paying stocks by tax-advantaged investors is matched by the supply from tax-disadvantaged investors. Second, markets are not efficient to depict any instantaneous reaction. Third, our methodology cannot isolate the effect of a single announcement made as part of a series of announcements. Lastly, there is a time lag before we witness investor reactions. Our results rule out all four alternative explanations. We conclude that dividend taxes are not an important criterion for investors to effect instantaneous stock price reactions.